Emerging roles of non-coding RNAs in fibroblast to myofibroblast transition and fibrotic diseases - Xing, Xuewu; Rodeo, Scott A. (Frontiers in Pharmacology, 2024)
The transition of fibroblasts to myofibroblasts (FMT) represents a pivotal process in wound healing, tissue repair, and fibrotic diseases. This intricate transformation involves dynamic changes in cellular morphology, gene expression, and extracellular matrix remodeling. While extensively studied at the molecular level, recent research has illuminated the regulatory roles of non-coding RNAs (ncRNAs) in orchestrating FMT. This review explores the emerging roles of ncRNAs, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), in regulating this intricate process. NcRNAs interface with key signaling pathways, transcription factors, and epigenetic mechanisms to fine-tune gene expression during FMT. Their functions are critical in maintaining tissue homeostasis, and disruptions in these regulatory networks have been linked to pathological fibrosis across various tissues. Understanding the dynamic roles of ncRNAs in FMT bears therapeutic promise. Targeting specific ncRNAs holds potential to mitigate exaggerated myofibroblast activation and tissue fibrosis. However, challenges in delivery and specificity of ncRNA-based therapies remain. In summary, ncRNAs emerge as integral regulators in the symphony of FMT, orchestrating the balance between quiescent fibroblasts and activated myofibroblasts. As research advances, these ncRNAs appear to be prospects for innovative therapeutic strategies, offering hope in taming the complexities of fibrosis and restoring tissue equilibrium.